The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1038/ng1292-301
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic stability and genotype – phenotype correlation of the trinucleotide repeat in X–linked spinal and bulbar muscular atrophy

Abstract: Expansion of the trinucleotide repeat (CAG)n in the first exon of the androgen receptor gene is associated with a rare motor neuron disorder, X-linked spinal and bulbar muscular atrophy. We have found that expanded (CAG)n alleles undergo alteration in length when transmitted from parent to offspring. Of 45 meioses examined, 12 (27%) demonstrated a change in CAG repeat number. Both expansions and contractions were observed, although their magnitude was small. There was a greater rate of instability in male meio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
149
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 344 publications
(160 citation statements)
references
References 19 publications
10
149
0
Order By: Relevance
“…However, one of the poorly understood features of expansion is the gender bias that is associated with transmission. Large changes in repeat number are known to be transmitted through the paternal line in HD (1, 2), SCA1 (3), dentatorubral-pallidoluysian atrophy (DRPLA) (4), MachadoJoseph disease (5), and spinal and bulbar muscular atrophy (SBMA) (6) and through the maternal line in Fragile X (7,8). The gender bias transmission has also been documented in transgenic mice (9 -12).…”
mentioning
confidence: 99%
“…However, one of the poorly understood features of expansion is the gender bias that is associated with transmission. Large changes in repeat number are known to be transmitted through the paternal line in HD (1, 2), SCA1 (3), dentatorubral-pallidoluysian atrophy (DRPLA) (4), MachadoJoseph disease (5), and spinal and bulbar muscular atrophy (SBMA) (6) and through the maternal line in Fragile X (7,8). The gender bias transmission has also been documented in transgenic mice (9 -12).…”
mentioning
confidence: 99%
“…In SBMA patients, a normally polymorphic CAG repeat (10 -36 CAGs) expands to 38 -66 CAGs. The number of CAGs is inversely correlated with the age of onset of the disease (2)(3)(4). To date, seven other CAG repeat diseases have been identified, including Huntington's disease (5), dentatorubralpallidoluysian atrophy (6,7), and five spinocerebellar ataxias: 1, 2, 3, 6, and 7) (8 -14).…”
mentioning
confidence: 99%
“…To prevent misdiagnoses, we simultaneously applied two genotyping methods: a direct analysis for the number of CAG repeats in exon 1 of the AR gene and sex determination by amplification of the SRY gene to diagnose SBMA. SBMA is caused by an expansion of the CAG repeat in exon 1 of the AR gene, and individuals with more than 40 CAG repeats should be diagnosed with SBMA; the average CAG repeat length from patients with SBMA is 47 CAGs [29]. Patients with SBMA have two important clinical features, one is slowly progressive weakness and atrophy in the limb and bulbar muscles and the other one is androgen insensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with SBMA usually present muscle weakness in their midforties [32]. However, the age of disease onset correlates inversely with the CAG repeat length, i.e., greater CAG repeat lengths correspond to earlier disease onset [29]. Christopher Grunseich et al reported a 29-year-old patient with SBMA who had 68 CAG repeats in the AR gene and who had presented weakness since age 18 [14].…”
Section: Discussionmentioning
confidence: 99%